Analysis of Control Characteristics and Design of Control System Based on Internal Parameters in Doubly Fed Variable-Speed Pumped Storage Unit. (17th June 2021) - Zhao, Guopeng; Zhang, Yongxin; Ren, Jiyun
Abstract : In this paper, the control strategies and their characteristics when applied to the doubly-fed variable-speed pumped storage unit in generating mode and pump mode are discussed. The composition of doubly fed variable-speed pumped storage unit is introduced, and the mathematical model of every component is proposed. Two control strategies of the unit are introduced. One is the power priority control strategy and the other is the speed priority control strategy. Then, the control block diagrams of the two control strategies in the generating mode and the pump mode are established, and the parameters of the unit in each control strategy are designed. The two control strategies are simulated in power generation and pumping conditions. Finally, the conclusion that power priority strategy has a better effect on power control is obtained.